Training for Making Herbarium Learning Media in Elementary Science Learning - Dhamas Mega Amarlita; Mawar Indayani (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Abstract: This community service activity (PKM) aims to: 1) provide understanding to teachers about creative and innovative learning media; 2) provide guidance to teachers on the procedure for selecting the use of media according to the level of development of students; and (3) providing guidance in making and learning herbarium in elementary science learning. This activity involved all teachers of SD Negeri 2 Tulehu which was carried out in two stages. The first stage is to provide exposure and discussion and the second stage is to create an elementary science herbarium learning model. The substance given in the first stage in the presentation and discussion is the understanding and types of learning media, how to select learning media appropriately and well, learning media, herbarium learning media and how to make them. Keywords: media, learning, herbarium, science